(untitled) (Revista Contexto & Educação, 2026)
This article presents the findings of a study that integrated Mediated Learning Experience (MLE) and Excellent Thinking as theoretical-methodological frameworks for analyzing critical and creative thinking in Science Education. Conducted with sixth-grade students, the investigation developed qualitative parameters to identify manifestations of this type of thinking in written productions about the Earth’s interior. The results indicate that the articulation between MLE and Excellent Thinking proved consistent in characterizing evidence of criticality and creativity in students’ interpretations. It is concluded that this integration expands the possibilities for the qualitative analysis of excellent thinking within the context of science education.